A strategy to locally optimize the material composition of AM construction elements - Craveiro, F. (2016)
New technologies and rising customer expectations are motivating key improvements in the construction sector towards more integrated and organic systems using novel computational fabrication processes. Natural systems are dependent upon stress or strain requirements where the material properties are optimally distributed. Using heterogeneous composite materials with a variable material distribution for distinct functional requirements, similar to natural structures, will enable to model, simulate and fabricate construction elements with specific loading conditions. This work has developed a strategy to optimize material composition, through an algorithm editor combined with a FEM software. The code was created to locally adjust a multi-material ratio according to the Von Mises stress map, simulating nature’s structural behavior, to produce functional graded construction elements. A concept wall prototype was tested as a case study, to explore the variation of material porosity. Further developments will enable to directly control the additive manufacturing equipment.